THERAPY CONNECT - De Paula Inocêncio, Guilherme; Chagas Siqueira, Breno; Amaral Dos Santos , Emanuel; Augusto Siqueira Maia , Guilherme; Alves Morais, Luiz Fernando; Pinto de Oliveira Filho , Reginaldo; Santos Faria Silva , Talles; Murillo Siqueira Teodoro, Thales (CIPEEX, 2024)
THE "THERAPY CONNECT" APPLICATION REPRESENTS A GROUNDBREAKING PLATFORM DESIGNED TO REVOLUTIONIZE HOW PSYCHOLOGISTS COMMUNICATE WITH THEIR PATIENTS. ITS PRIMARY GOAL IS TO MAKE THIS INTERACTION MORE ACCESSIBLE AND EFFECTIVE. THIS SOLUTION PROVIDES A SECURE AND USER-FRIENDLY ENVIRONMENT FOR PSYCHOLOGISTS TO SCHEDULE APPOINTMENTS, EXCHANGE CONFIDENTIAL MESSAGES, EVALUATE SESSIONS, AND PROVIDE ACCESS TO EDUCATIONAL RESOURCES RELATED TO MENTAL HEALTH. WITH A MISSION TO SIMPLIFY ACCESS TO PSYCHOLOGICAL ASSISTANCE AND OFFER MORE PERSONALIZED THERAPEUTIC SUPPORT, THE APPLICATION AIMS TO CREATE A POSITIVE EXPERIENCE FOR BOTH MENTAL HEALTH PROFESSIONALS AND INDIVIDUALS SEEKING PSYCHOLOGICAL SUPPORT.